2000
DOI: 10.1002/cjce.5450780505
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities when using a standard (T/3) rushton turbine for stirring as foam disruption (SAFD)

Abstract: n the fermentation industry, the formation of foam during the fermentation process can lead to blockage of the outlets and reduce I the productive volume. Foam can be broken mechanically, through the installation of a foam disrupter, but the installation and operation of such a system can be costly. Another much used method is the addition of anti-foam, which however leads to a reduction in kp and consequently in oxygen transfer capacity (van't Riet and Tramper, 1991). A novel approach is the use of the upper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In previous work, the tip speed ranged from 2.5 to 5 m/s, as occurs on a large scale [6]. Boon et al [2] suggested that the D/T ratio was fairly high, i.e. up to 0.6, for the laboratory experiments on SAFD by Hoeks et al [6].…”
Section: Mediummentioning
confidence: 96%
See 4 more Smart Citations
“…In previous work, the tip speed ranged from 2.5 to 5 m/s, as occurs on a large scale [6]. Boon et al [2] suggested that the D/T ratio was fairly high, i.e. up to 0.6, for the laboratory experiments on SAFD by Hoeks et al [6].…”
Section: Mediummentioning
confidence: 96%
“…However, P g /P u values of 0.2 are low for upper Rushton turbines as they are normally in the range of 0.5 and higher [16]. These very low values are probably due to increased gas entrainment when applying SAFD with the standard Rushton turbine (D/T=0.33) [2]. The observed range of P g /P u (see Table 4) related well to the measured range in gas hold-up (see Table 6 and below), i.e.…”
Section: Power Draw During Safdmentioning
confidence: 99%
See 3 more Smart Citations